The Beginning of Reforms in the Educational System in Turkestan at the End of the XIX Century at the Beginning of the XX Century - Bahritdinovna, Sadiyeva Rohat; Salahitdinovna, Tilavova Shakhnoza (Buletin Antropologi Indonesia, 2025)
The end of the 19th century the beginning of the 20th century was a period of global change in the territory of Central Asia. The conquest of the territory by the Tsarist race and the introduction of a system of a different culture influenced all spheres of social life, forming over many centuries and creating many changes in the settled lifestyle. In particular, the establishment of new method schools, implemented by representatives of the local progressive movement in the educational system, harmonizing European educational methods and achievements with the Muslim education system, made a sharp turn in the field of Education. This article will cover the renewal of the teaching system in the schools of the new method founded by progressives, the introduction of secular subjects, increased attention to the education of girls, the development of methodological manuals and textbooks, and changes in the educational system.